"Everybody Was Looking for a Good Government Job": Occupational Choice during Segregation in Arlington, Virginia. (July 2014) - Perry, Nancy; Reybold, L. Earle; Waters, Nigel
During the period from childhood through young adulthood individuals select the occupation that best satisfies their needs based on their values, interests, education, and environment. Arlington County, Virginia, provides an opportunity to study the impact that geography played on occupational choice for one black community during segregation. Using qualitative methods, this article explores the occupational choices of Arlington's African Americans as Arlington grew from a scattering of farm settlements to a prosperous white suburb of Washington, D.C. Washington's black high schools offered excellent career training and the government offered Civil Service employment. The arrival in Arlington of the Pentagon building and large numbers of white federal workers provided new sources of employment but obliterated existing farm and factory work. The article concludes that Arlington's geography, that is, its proximity to the federal government in Washington, had both a positive and a negative influence on Arlington's African Americans when choosing their occupations.